PROSPEK USAHA PEMBESARAN LELE SANGKURIANG PROBIOTIK DI DESA SUKOSARI KECAMATAN BELITANG KABUPATEN OKU TIMUR - Aisah (Jurnal Bakti Agribisnis, 2015)
The purpose of this research were to : (1) To know the cost, income and income obtained by farmers on the cultivation of sangkuriang catfish probiotics in Sukosari Belitang OKU Timur, (2) To know the feasibility of cultivation business of sangkuriang catfish probiotik in Sukosari Belitang OKU Timur. This research was conducted in Sukosari Village, Belitang Sub-District, East OKU Regency. The selection of the location of this study is determined purposively with the consideration that in Sukosari Village there are some farmers who do cultivation of catfish sangkuriang by using probiotics to increase the productivity of catfish. This research was conducted in March 2014. This study found that the total cost of production issued in the cultivation of catfish sangkuriang probiotik in one production cycle is Rp 15.175.709, the total revenue during one production cycle is Rp 20,886,042 so that Income received amounted to Rp 5,710,333. The value of R / C ratio is 1.37 shows the cultivation of probiotic sangkuriang catfish, and the NPV value is Rp 21,082,125, the IRR value is 39.79% and the Net B / C value is 1.79 indicating Cultivation of catfish sangkuriang probiotik feasible (feasible) to be developed.